Brutons tyrosine kinase inhibition to suppress mast cell activation in atherosclerosis. (10th June 2022) - Hemme, E; Delfos, L; Depuydt, MAC; Bernabe Kleijn, MNA; Schaftenaar, FH; Foks, AC; Kuiper, J; Bot, I
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Dutch Heart Foundation Aim: Acute cardiovascular diseases, such as myocardial infarction or stroke, are still a major cause of death in Western Society. The main underlying pathology of cardiovascular diseases is atherosclerosis, which is caused by the accumulation of lipids and inflammatory cells in the vessel wall, in so-called atherosclerotic plaques. Mast cells accumulate within these atherosclerotic plaques and activation of mast cells leads to the progression and destabilization of advanced plaques via the secretion of pro-inflammatory mediators and cytokines. Mast cells can be activated by various stimuli, of which crosslinking of the Fcε receptor I (FcεRI) with IgE-antigen complexes is best known. Bruton's tyrosine kinase (BTK), a cytoplasmic nonreceptor tyrosine kinase, is involved in the downstream signaling of FcεRI-mediated mast cell activation and degranulation. Therefore, BTK might be an attractive target to interfere in the FcεRI-mediated mast cell activation pathway. In this study, we thus aimed to assess the effects of the BTK inhibitor ACP-196 on FcεRI-mediated mast cell activation, plaque progression and destabilization in an atherosclerotic mouse model. Methods and Results: Male LDLr knockout mice, 7-11 weeks old, were treated with ACP-196 (25 mg/kg p.o., n=15) or control solvent (n=14) three times per week for eight weeks. During treatment, mice were fed a Western-type diet (WTD) to induce atherosclerotic plaque formation. During the experiment, plasma total cholesterol levels and body weight did not differ between the control and treatment group. After eight weeks, mice were sacrificed and hearts were isolated to determine atherosclerotic plaque size and stability in the aortic root by histology. Other immunological relevant tissues, such as aorta, spleen and mediastinal lymph nodes were harvested to examine mast cell activation status and other immune cells by flow cytometry. After eight weeks of ACP-196 treatment in LDLr knockout mice, a significant 59% reduction in the frequency of CD117+ FcεRI+ mast cells was observed in aortic plaques of ACP-196 treated mice (0.24±0.06%) compared to control mice (0.57±0.08%, p<0.05), while relative mast cell activation status was not affected. Additionally, ACP-196 treatment inhibited B cell maturation in the circulation, spleen, mediastinal lymph nodes and peritoneal cavity of LDLr knockout mice compared to control mice. However, these effects on immune cells did not translate into effects on atherosclerosis, as ACP-196 treatment (size:12.3±2%; collagen:14.5±1.9%) did not significantly affect atherosclerotic plaque size and collagen content when compared to control mice (size:11.5±1.4%; collagen: 13.6±1.5%). Conclusions: Conclusively, these findings suggest that ACP-196 treatment leads to reduced migration of mast cells to the atherosclerotic plaques of LDLr knockout mice, but does not directly affect mast cell activation and initial atherosclerotic lesion development.